Desensitization of 5-HT-1A Somatodentritic Receptors in Tryptophan Treated and Co-treated Rats Induced by Methylphenidate - Farhan, Muhammad; Riaz, Fatima; Wali, Sana; Rafiq, Hamna (Current Clinical Pharmacology, 2019)
Background: Psychostimulants can induce behavioral sensitization by their chronic use. The main target for the action of these drugs is dopamine, neither epinephrine nor serotonin transporters. Serotonin is synthesized by the precursor L-tryptophan. Tryptophan and methylphenidate being 5-HT agonists, both increase the level of serotonin thereby causing desensitization of 5-HT1a receptors. The present study investigated whether behavioral sensitization induced by Methylphenidate is decreased in tryptophan administrated animals. Methods: The Experiment was divided into 2 phases (1). Behavioral effects of repeated administration of TRP 100 mg/kg and MPD for 14 days in three groups; (i) water (ii) MPD 1.0 mg/kg (iii) TRP. To explore the locomotor effects of treatment, the activity was monitored in a familiar and novel environment. (2) Behavioral consequences of repeatedly administrated MPD (1.0 mg/kg) on pretreated TRP (100 mg/kg) and MPD (1.0 mg/kg) animals following Co-MPD and TRP for 14 days, rats were divided in three groups (i) water, (ii) MPD and (iii) TRP as mentioned in Experiment no 1. After two weeks six subgroups were assigned i.e. (i) water-saline, (ii) water- MPD, (iii) TRP-saline (iv) TRP-MPD (v) MPD-saline and (vi) MPD-MPD+TRP and treated for further 14 days. Locomotor behavior was monitored in familiar environment on the next day and in novel environment on alternate days of each administration. Results: The Results from phase 1 showed increased activity in both (TRP and MPD) treatments. However, the results of phase 2 showed significant decrease in methylphenidate-induced behavioral sensitization by both pretreatment and co-administration with TRP. Conclusion: The present study suggests the potential of tryptophan to decrease the risk of behavioral sensitization induced by methylphenidate.
Keywords: tryptophan